The Importance of Mahatma Respiratory Sports in Maintaining Body Health and Fitness - Achmad Kholiqi; Retno Widyani; Nuniek Setia Sukmayani; Taufik (Jurnal Abdisci, 2024)
Mahatma is a respiratory science that has a tremendous influence on health. By processing Mahatma's breathing, various diseases can be treated very quickly. Various physical diseases that have been proven to be treated very rapidly through this Mahatma breathing exercise include asthma, allergies, ulcers, high blood pressure, low blood pressure, heart, diabetes (diabetes erupts), stone urine, kidney, liver, hemorrhoids, sinusitis, migraine, vertigo, impotence, frequent colds, soreness, fatigue, motion sickness, and various other physical ailments. Even by following this Mahatma breathing exercise, we will be free from the habit and dependence of using drugs. In addition, by following Mahatma's breathing exercises, emotions become more controlled, so angry and irritable people will become more patient. Likewise, stress will disappear and turn into self-confidence and happiness. As for those who are already healthy, with Mahatma, breathing exercises will make our bodies stronger so that we can work harder with enthusiasm. The strength-trained is the power of dhikr, kicks, and breath.